Retrospective investigation of the prognostic value of the β1 integrin expression in patients with head and neck squamous cell carcinoma receiving primary radio(chemo)therapy - Cordes, Nils (PLoS One, 2018)
This retrospective study evaluated the expression of β1 integrins and associated proteins as prognostic markers for primary radio(chemo)therapy outcome of patients with locally advanced head and neck squamous cell carcinomas (HNSCC). Tissue microarrays were prepared from 224 HNSCC patients undergoing curative primary radio(chemo)therapy from 1996 to 2005. Staining intensities of β1 integrin and its downstream-proteins FAK, phosphorylated FAK as well as the β1 integrin ECM ligands fibronectin and collagen type-I were determined. Their association to the primary endpoint loco-regional control and the secondary endpoints overall survival and freedom from distant metastasis was analyzed by Cox regression. None of the considered molecular parameters showed a significant association with loco-regional control and freedom from distant metastasis. Patients with p16 positive tumors or tumors with a low intensity of fibronectin showed significantly higher overall survival in univariable regression. In multivariable regression including additional clinical parameters, however, these parameters were not significantly associated with overall survival. Our study in a HNSCC patient cohort treated with primary radio(chemo)therapy does not reveal a prognostic value of β1 integrin expression.